Cost Overrun Factors in Construction Projects: A BIM and SEM Analysis - Al Ahmad, Muhammad Hijerah; Arifuddin, Rosmariani; Abdurrahman, M. Asad (Engineering, Technology & Applied Science Research, 2026)
This research addresses the phenomenon of cost overruns with the following objectives: (i) identifying cost overrun factors using a Building Information Modeling (BIM) application approach, (ii) analyzing the causality model of these factors, and (iii) applying the BIM method to manage cost overruns. Data collection was conducted through relevant research, followed by determining the variables, indicators, and respondent criteria. Expert validation of the variables was then carried out. Finally, a perception survey was conducted using a questionnaire, and the data were processed using the Structural Equation Modeling (SEM) method with SmartPLS software. According to the results, two variables had a significant effect, namely implementation and working relationships (X1 = 0.325) and natural environment (X9 = 0.271). Meanwhile, the other eight variables showed a minor effect on cost estimates, such as finance (X6 = 0.118), economic feasibility (X8 = 0.041), labor (X5 = 0.027), equipment (X4 = 0.025), materials (X3 = 0.021), unexpected aspects (X10 = 0.018), project documentation aspects (X2 = 0.006), and implementation time, which showed a zero effect (X7 = 0.00). The novelty of this research lies in the integration of BIM and SEM to quantitatively analyze cost overrun factors in Indonesian building projects, providing insights into minimizing cost overruns in construction projects.